2016
DOI: 10.1051/epjconf/201611701003
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to the island of stability of super-heavy elements search

Abstract: It is expected that the cross section for super-heavy nuclei production of Z > 118 is dropping into the region of tens of femto barns. This creates a serious limitation for the complete fusion technique that is used so far. Moreover, the available combinations of the neutron to proton ratio of stable projectiles and targets are quite limited and it can be difficult to reach the island of stability of super heavy elements using complete fusion reactions with stable projectiles. In this context, a new experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…In some earlier work on this problem we used the Big-Sol Superconducting-Solenoid Time of Flight Spectrometer at Texas A & M to perform several surveys of projectile target combination and bombarding energy for collisions of 86 Kr, 136 Xe and 197 Au with 232 Th in an effort to identify good candidate reactions for heavy and super-heavy element production [54][55][56][57][58]. Those experiments, at higher laboratory energies per nucleon than the present work, indicated the possible production of heavy elements with Z above 100 [58]. However the experiment was discontinued when the spectrometer developed a He leak which made it not possible to sustain the necessary magnetic field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some earlier work on this problem we used the Big-Sol Superconducting-Solenoid Time of Flight Spectrometer at Texas A & M to perform several surveys of projectile target combination and bombarding energy for collisions of 86 Kr, 136 Xe and 197 Au with 232 Th in an effort to identify good candidate reactions for heavy and super-heavy element production [54][55][56][57][58]. Those experiments, at higher laboratory energies per nucleon than the present work, indicated the possible production of heavy elements with Z above 100 [58]. However the experiment was discontinued when the spectrometer developed a He leak which made it not possible to sustain the necessary magnetic field.…”
Section: Methodsmentioning
confidence: 99%
“…We then adopted a new direction for investigation of such reactions based upon the implantation of heavy reaction products in a downstream catcher foil and the detection of alpha particle decays characteristic of heavy nuclei. For this purpose the Jagellonian University Group constructed a forward array of 63 active catcher (AC) fast plastic scintillator detectors and dedicated state-of-the-art fast timing electronics to function as a time filter for recoil implantation and alpha decay detection [57,58]. Tests employing these plastic scintillators demonstrated that the use of such a time filtering device was feasible even in the harsh environment encountered in the experiments envisaged.…”
Section: Methodsmentioning
confidence: 99%
“…One fascinating set of studies of the synthesis of very heavy nuclei by MNT are the studies of Natowitz et al [75][76][77][78] at Texas A&M. In a series of seminal papers from 2011 to 2018, these authors describe the possible formation of very heavy nuclei in MNT reactions. The initial publication of this group [75] described a study of the 7.5 A MeV 197 Au + 232 Th reaction.…”
Section: Mnt Reactions-heavy Transfer Productsmentioning
confidence: 99%
“…The authors were cautious and expressed the need for further work to confirm this remarkable result ( Z = +10). Further details of this experiment were presented in Majka et al [76] along with plans to use an "active" catcher setup for further studies [77]. Wuenschel et al [78] reported the results of an investigation of the 238 U + 232 Th reaction at projectile energies of 6.1-7.5 A MeV.…”
Section: Mnt Reactions-heavy Transfer Productsmentioning
confidence: 99%